2002
DOI: 10.1051/0004-6361:20020293
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectra from accretion disks illuminated by protons

Abstract: Abstract. The X-ray spectrum from a cool accretion disk heated by virialized protons is computed. The cool disk is either embedded in a magnetically heated accretion disk corona or partly extends into an ion supported torus (or ADAF). We calculate the stationary equilibrium between proton heating, electron thermal conduction and the radiative losses by bremsstrahlung and Compton scattering. A heated surface layer on top of the accretion disk is produced with temperatures between 60-90 keV above a cool layer wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…In addition to this purely radiative interaction, the hot flow also heats the cool disk by "proton illumination" (Deufel et al 2001;Deufel et al 2002;. In this process, part of the ISAF condenses onto the disk in the overlap region.…”
Section: Geometry and Soft Photon Sourcesmentioning
confidence: 99%
“…In addition to this purely radiative interaction, the hot flow also heats the cool disk by "proton illumination" (Deufel et al 2001;Deufel et al 2002;. In this process, part of the ISAF condenses onto the disk in the overlap region.…”
Section: Geometry and Soft Photon Sourcesmentioning
confidence: 99%
“…A fully relativistic treatment of the Coulomb interactions in a plasma has been given by Stepney & Guilbert (1983). We have compared the classical treatment according to Spitzer's theory with this relativistic result in Deufel et al (2001Deufel et al ( , 2002, and found it to be accurate to better than 5% for proton temperatures <100 MeV. The classical approximation in Spitzer's analysis therefore does not introduce a significant error for the problem considered here.…”
Section: Corrections At High and Low Energiesmentioning
confidence: 90%
“…Radiative coupling was investigated by Haardt & Maraschi (1991, 1993 in the context of their "twophase model" for the hard X-ray spectra of accreting black holes. Explanation of these spectra as resulting from the coupling between an ISAF and a cool disk via hot the protons was proposed by Spruit (1997) and Spruit & Haardt (2000), and studied in greater detail by Deufel & Spruit (2000) (henceforth Paper I) and Deufel et al (2002) (henceforth Paper II). The physics of this process has been studied before in the context of accretion onto a neutron star surface by Zel'dovich & Shakura (1969), Alme & Wilson (1973), Deufel et al (2001).…”
Section: A "Warm" Surface Layer On the Cool Diskmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy from the protons is sufficient to evaporate the upper layers of the disk into a hot corona (called here the "hot layer"), whose temperature is set by a balance between heating from the ions and cooling, predominantly through inverse Compton scattering of disk photons. The work in (13) found that the optical depth of the hot layer is around unity, varying only weakly with irradiating flux and distance from the hole.…”
Section: Pos(mqw7)010mentioning
confidence: 99%